Silencing Long Non-coding RNA Kcnq1ot1 Limits Acute Kidney Injury by Promoting miR-204-5p and Blocking the Activation of NLRP3 Inflammasome - JunTao Wang (Frontiers Media S.A., 2021)
Acute kidney injury (AKI) is a critical clinical disease characterized by an acute decrease in renal function. Long non-coding RNAs (LncRNAs) are important in AKI. This study aimed to explore the mechanism of lncRNA Kcnq1ot1 in AKI by sponging microRNA (miR)-204-5p as a competitive endogenous RNA (ceRNA). AKI mouse model and hypoxia/reoxygenation (H/R) model of human kidney (HK) cells were established. Kcnq1ot1 expression, cell proliferation, and apoptosis were measured. Binding relations among Kcnq1ot1, miR-204-5p, and NLRP3 were verified. Pathological changes and cell apoptosis were detected. The results showed that Kcnq1ot1 was highly expressed in the AKI model in vivo and in vitro. Kcnq1ot1 knockdown promoted cell proliferation and prevented apoptosis and inflammation. Furthermore, Kcnq1ot1 inhibited miR-204-5p expression by competitively binding to miR-204-5p in HK-2 cells. miR-204-5p targeted NLRP3 and NLRP3 overexpression averted the inhibiting effect of miR-204-5p on apoptosis and inflammation in HK-2 cells in vitro. Kcnq1ot1 knockdown in vivo promoted miR-204-5p expression, inhibited NLRP3 inflammasome activation, reduced levels of SCr, BUN, and KIM-1, and thus alleviated AKI and reduced apoptosis. In summary, silencing lncRNA Kcnq1ot1 inhibited AKI by promoting miR-204-5p and inhibiting NLRP3 inflammasome activation.